(untitled) (World Economics and Finance Bulletin, 2024)
The purpose of this research is to determine the impact of Person - Environment fit on enhancing adaptive performance at the level of a sample of workers in cement factories in Iraq and its reflections on work outputs. This study relied on the scales and dimensions established by (Kristof et al., 2005) to measure Person - Environment fit and (Pulakos et al., 2000) to measure Adaptive Performance. Since the research used the questionnaire with the purpose of gathering information, the study’s sample included 160 individuals in the Al-Duh and Saman Cement Factory in Iraq. Path analysis was used to test the hypotheses, along with multiple regression and confirmatory factor analysis. A number of results were reached, the most prominent of which is that the Fit between the person in relation to their surroundings contributes to enabling organizations to build a dynamic work environment. This fit affects the enhancement of harmony between the individual and the organization, which in turn positively reflects on adaptive performance by improving personal efficiency, creativity and innovation, and the ability to flexibly adapt to new situations and find alternative solutions, whether in work or daily life.